Analysis Of Public Perceptions of Online Zakat Payments Through the Bank Syariah Indonesia Mobile Application - Zuliani, Rafiza; Bayduri, Intan; Agustinar, Agustinar; Kamal, Safwan; Kumalahayati, Nur (Journal of Contemporary Applied Islamic Philanthropy, 2024)
Purpose: This study aims to determine the online zakat payment procedures in the Bank Syariah Indonesia Mobile application and public perceptions and constraints related to online zakat payments through the Bank Syariah Indonesia Mobile application. Methodology: The method used is a qualitative approach. Data collection techniques using observation, interviews, and documentation. The informants in this study were the people of Gampong Meutia, Langsa Kota District. Findings: The results of the study show that public perceptions regarding online zakat payments through the Bank Syariah Indonesia Mobile application tend to lack trust and do not believe in the clarity of zakat distribution later and the public believes that direct zakat payments are far more effective because they can know the mustahik, in contrast to online zakat payments where the muzakki does not know for sure about the mustahik who will receive the zakat. However, it is different from the perception of the people who have used the BSI Mobile application in paying their zakat, where based on the experience they have, the perception created is that there is convenience from the BSI Mobile application in making zakat payments without having to provide a special time in fulfilling these Muslim obligations.